Early detection of neck lymph node metastases in breast cancer patients: the role of ultrasound and fine needle biopsy - Rebol, Janez; Balon, Peter; Kokol, Peter; Lanišnik, Boštjan; Takač, Iztok; Dovnik, Andraž; Fokter Dovnik Nina; Sobočan, Monika; Arko, Darja (Acta Medico-Biotechnica, 2021)
Purpose: To analyze the distribution and pattern of neck metastasis in breast cancer (BC) patients. Methods: The clinicopathological characteristics of 41 patients with BC and confirmed neck metastasis (NM) treated at our institution between 2010 and 2016 were retrospectively analyzed by reviewing medical records. The diagnosis of NM was confirmed by fine needle aspiration cytology, and node localization was classified into six levels according to Robbins’ classification. Statistical analysis was performed using descriptive statistics, Pearson’s correlation and multidimensional correspondence analysis. All statistical analyses were performed using SPSS. Results: At the time of neck ultrasonography, 34 (85%) patients had developed distant metastases, 38% of the patients were asymptomatic, and 17% had no palpable nodes. The average time from BC diagnosis to the development of NM was 5.8 years (range, 0–26 years). Lymph node metastasis occurred at level V in 53.7% of patients and level IV in 19.5% of patients. Two-level involvement occurred in 9.8% and one-level involvement in 75% of patients. There were significant correlations (p < 0.01) between patient age and time from diagnosis to development of NM, age and stage of the disease, and stage and appearance of conglomerates. Conclusion: The most common site of NM from BC was next to the supraclavicular fossa, although they occurred at other levels. Ultrasonography combined with fine needle aspiration cytology is effective for the detection of early occult metastatic lymph nodes.